Modeling Climate Impacts on Tree Growth to Assess Tree Vulnerability to Drought During Forest Dieback - Valeriano, Cristina; Gazol, Antonio; Colangelo, Michele; González de Andrés, Ester; Camarero, J. Julio (Frontiers in Plant Science, 2021)
Forest dieback because of drought is a global phenomenon threatening particular tree populations. Such vulnerable stands are usually located in climatically stressing locations as xeric sites subjected to seasonal drought. These tree populations show a pronounced loss of vitality, growth decline and high mortality in response to extreme climate events such as heat waves and droughts. However, dieback events do not uniformly affect stands with some trees showing higher symptoms of drought vulnerability than other neighboring conspecifics. We investigated if trees showing different vulnerability to dieback showed lower growth rates and higher sensitivity to climate in the past by using dendroecology and the Vaganov-Shashkin process-based growth model. We studied two Pinus pinaster stands with contrasting growth rates showing recent dieback in the Iberian System, north-eastern Spain. We compared coexisting declining (D) and non-declining (ND) trees with crown defoliation values above and below the 50% threshold, respectively. The mean growth rate was lower in D than in ND trees in the two stands. The two vigor classes showed a growth divergence prior to the dieback onset and different responsiveness to climate. ND trees were more responsive to changes in spring water balance and soil moisture than D trees indicating a loss of growth responsiveness to climate in stressed trees. Such interaction between water availability and vigor was reflected by the VS-model simulations which evidenced that growth was mainly limited by low soil moisture in both sites. The presented comparisons indicate different stand vulnerability to drought contingent on site conditions. Further research should investigate the role played by environmental conditions and individual features such as the access to soil water or hydraulic traits and implement them in process-based growth models to better forecast dieback.